2017
DOI: 10.1186/s12939-017-0662-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender, childhood and adult socioeconomic inequalities in functional disability among Chinese older adults

Abstract: BackgroundGender difference and life-course socioeconomic inequalities in functional disability may exist among older adults. However, the association is less well understood among Chinese older population. The objective is to provide empirical evidences on this issue by exploring the association between gender, childhood and adult socioeconomic inequalities in functional disability.MethodsData from the 2013 wave of the China Health and Retirement Longitudinal Study (CHARLS) was utilized. Functional disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 42 publications
5
63
0
2
Order By: Relevance
“…Among our participants, older women seemed more vulnerable to accumulated deficits than older men, as another study also found [37]. Women's tendency to become severely frail in later life could be explained by their higher probability of functional disability, which is a main measure of physical deficits [38]. Our results also suggested that participants with lower educational attainment were more likely to be severely frail, which was in agreement with a previous study that older adults with lower educational attainment were at increased risk of worsening frailty over a 2-year period [39].…”
Section: Discussionsupporting
confidence: 55%
“…Among our participants, older women seemed more vulnerable to accumulated deficits than older men, as another study also found [37]. Women's tendency to become severely frail in later life could be explained by their higher probability of functional disability, which is a main measure of physical deficits [38]. Our results also suggested that participants with lower educational attainment were more likely to be severely frail, which was in agreement with a previous study that older adults with lower educational attainment were at increased risk of worsening frailty over a 2-year period [39].…”
Section: Discussionsupporting
confidence: 55%
“…Besides, a series of independent variables included in CHARLS dataset were taken into account based on a comprehensive literature review [3,5,8,[19][20][21][22][23][24][25][26]. A set of variables were included to identify the long-term effect of childhood environment and health.…”
Section: Other Covariatesmentioning
confidence: 99%
“…Based on previous literature (26,(34)(35)(36)(37)(38)(39)(40)(41)(42), several socio-demographic and clinical characteristics were included in the analyses as covariates because they have shown associations with ADL and/or different aspects of housing in people with PD or older adults.…”
Section: Other Covariatesmentioning
confidence: 99%